Rockin' around the chickadee ebook - Andrews, Donna (Meg Langslow Mystery, 2024)
Bells are ringing and alarms are sounding in Donna Andrews' latest cheery addition in the New York Times bestselling Meg Langslow series. Meg's sister-in-law, Delaney, is pregnant. Since her due date is on or around Christmas Day, this is putting a bit of a damper on the usual holiday festivities. Meg and Michael are NOT hosting the usual house full of relatives and parties. Instead, Meg, along with her mother, her grandmother, her cousin Rose Noire, and her good friend Caroline, are militantly doing everything they can think of to keep Delaney quiet and healthy. All the relatives are farmed out to friends and neighbors; all the parties are being held somewhere else; and while Delaney is bored and mutinous, she's doing well, and they're managing to maintain a serene, peaceful environment for her . . . until a body is found in Meg and Michael's yard. The body turns out to be an attendee at Presumed Innocent, a nearby conference that Meg's grandmother has organized. Some of the attendees want to learn how to exonerate a friend or family members who has been unjustly convicted, while the rest are avid true crime aficionados. And since the dead guy has been very vocal about his belief that most actual and would-be exonerees are guilty, guilty GUILTY!, nearly everyone at the conference dislikes him. But would any of them hate him enough to kill him? And can Meg still keep Delaney calm in the middle of a murder investigation, all while trying to catch the killer?